Gaining satisfaction and trust in a brand website - Zotos, Yorgos; Tsiotsou, Rodoula; Palla, Polyxeni (My University, 2014)
Gaining satisfaction and trust online remains a challenging task for marketers, due to increased levels of uncertainty that exist in the interactive environment. Many studies have been conducted in order to investigate how the online media influences satisfaction and trust (eg. Martin et al., 2011; Shankar et al. 2003). However, the present study makes an attempt to understand the factors that increase satisfaction and trust in an interactive brand website. In particular, the present study addresses the following two questions: Are the levels of consumer trust and satisfaction for a brand website different according to the level of website interactivity? Are the levels of consumer trust and satisfaction affected by the four facets (aesthetics, playfulness, service excellence and customer return on investment) of Experiential Value [EV].
Keywords: Gaining satisfaction; Trust; Interactive environment; Online media; Website; Website interactivity